Relation between Workload and Level of Complaints in the Musculoskeletal System through Nordic Body Map (NBM) on E.R. Nurses - Su’udi; Aby Yazid Al Busthomy Ro i’i; Titik Sumiatin; Wahyu Tri Ningsih; Teresia Retna Puspita Dewi; Wahyuningsih Triana Nugraheni (Institute of Medico-legal Publications Pvt Ltd, 2021)
Nurse workload is defined as all of the activities performed by a nurse while working in a nursing service unit.Work-related musculoskeletal disorder (WMSD) is a Musculoskeletal disorder (MSD) that becomes moresevere or lasts for a long time due to work-related activities. This study aims to determine the relationshipbetween the workload of emergency room nurses and the level of complaints in the musculoskeletal systemthrough the Nordic Body Map (NBM) method approach in every regional hospital in Tuban City. This studywas carried out using descriptive correlative study method with a cross sectional approach. The numberof respondents that participated in this study were 63 E.R. nurses who worked in regional hospitals inTuban City. Data was collected using a workload questionnaire and the Nordic Body Map (NBM) methodto determine the level of complaints of the musculoskeletal system. Data was then analyzed using ChiSquare test. Results showed that 54% of the respondents had moderate workload and no emergency nursesat hospitals in Tuban City had light workload. 44.4% of emergency nurses at hospitals in Tuban City hadsevere musculoskeletal complaints. According to this data, there is a relationship between the workload ofemergency room nurses and the level of complaints in the musculoskeletal system (P = 0.028). In conclusion,emergency nurses should keep an eye on their workload so that musculoskeletal problems do not occur.